Diamonds are a girl's best friend ebook A novel. - Colgan, Jenny (2020)
From beloved New York Times bestselling author Jenny Colgan, a heartwarming and hilarious comedy about a pampered London socialite forced to live life among the common folk. Sophie Chesterton is London's "It Girl". She knows all the right people, goes to all the right parties, and wears all the right clothes...and her rich parents pay for everything. But deep down she suspects that her best "friends"—and her posh lifestyle—are nothing but shallow fakes. Then one evening Sophie's life takes a shocking, drastic turn, and her father decides it's high time for the party girl to make her own way in the world. Forced to earn a meager living as a lowly assistant to a "glamour" photographer, live in a shabby flat with four smelly boys, and eat baked beans from the can—Sophie is desperate to get her old life back, at any cost. But does a girl really need diamonds to be happy? Full of warmth and sparkle, Diamonds are a Girl's Best Friend is a surprisingly winning tale about luxury, life lessons, and the surprisingly low cost of true happiness.